Minerals - M. P. Vaquero (Grasas y Aceites)
The possible changes in the mineral composition of food during frying could be the consequence of losses by leaching, or changes in concentrations caused by exchanges between the food and culinary fat of other compounds. The net result depends on the type of food, the frying fat used and the frying process. Moreover, the modifications that frying produces in other nutrients could indirectly affect the availability of dietary minerals. The most outstanding ones are those that can take place in the fat or in the protein. With respect to the interactions between frying oils and minerals, we have recent knowledge concerning the effects of consuming vegetable oils used in repeated fryings of potatoes without turnover, on the nutritive utilization of dietary minerals. The experiments have been carried out in pregnant and growing rats, which consumed diets containing, as a sole source of fat, the testing frying oils or unused oils. It seems that the consumption of various frying oils, with a polar compound content lower or close to the maximum limit of 25% accepted for human consumption, does not alter the absorption and metabolism of calcium, phosphorous, iron or copper. Magnesium absorption from diets containing frying oils tends to increase but the urinary excretion of this element increases, resulting imperceptible the variations in the magnesium balance. The urinary excretion of Zn also increased although its balance remained unchanged. Different studies referring to the effects of consuming fried fatty fish on mineral bioavailability will also be presented. On one hand, frying can cause structural changes in fish protein, which are associated with an increase in iron absorption and a decrease in body zinc retention. The nutritive utilization of other elements such as magnesium, calcium and copper seems to be unaffected. On the other hand; it has been described that an excess of fish fatty acids in the diet produces iron depletion, but when fatty fish is fried in olive oil the quality of the fish oil improves, enhancing the nutritive utilization of iron and other dietary minerals.